2012
DOI: 10.1108/17511871211268937
|View full text |Cite
|
Sign up to set email alerts
|

From unbalanced to balanced: performance measures in a Vietnamese hospital

Luu Trong Tuan

Abstract: PurposeFrom the data derived from a Vietnamese hospital, this study seeks to discern which organisational culture types, leadership styles, and trust types pave the path for the implementation of the balanced scorecard (BSC) system.Design/methodology/approachThe study uses a case research approach with a triangulation of data collation methods encompassing access to documents, field observations, and interviews. The in‐depth interviews with 37 hospital members and field observations were conducted during 21 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The relationship between behavioral factors of institutional investors and marketing effectiveness and brand performance can be another interesting research avenue (Luu, 2012a;Luu, 2012g;Luu, 2013f;Luu, 2012i). Behaviors of institutional investors as an important stakeholder group also can create sense of urgency for higher level of organizational change (Luu, 2012f;Luu, 2013d) and learning (Luu, 2012h;Luu, 2013g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between behavioral factors of institutional investors and marketing effectiveness and brand performance can be another interesting research avenue (Luu, 2012a;Luu, 2012g;Luu, 2013f;Luu, 2012i). Behaviors of institutional investors as an important stakeholder group also can create sense of urgency for higher level of organizational change (Luu, 2012f;Luu, 2013d) and learning (Luu, 2012h;Luu, 2013g).…”
Section: Resultsmentioning
confidence: 99%
“…The further research studies are also suggested to apply behavioral finance to explore the behavioral factors of institutional investors at the Stock Exchanges of Vietnam. Ethics should also be included into behavioral factors of institutional investors (Luu, 2012b;Luu, 2012d), especially those in industries in which ethics of stakeholders play a crucial role such as healthcare services (Luu, 2012e;Luu, 2012f;Luu, 2012g). The impact of corporate governance (Luu, 2011;Luu, 2012d;Luu, 2013b;Luu, 2013e) and corporate social responsibility (Luu, 2012d;Luu, 2012g;Luu, 2013a;Luu, 2013c) on behavioral factors of institutional investors can attract researchers as well.…”
Section: Resultsmentioning
confidence: 99%
“…HR flexibility data can be collected from reports from HR departments. Data on individual and collective job crafting, in some organizations, can be garnered through the individual and team performance indicators under the internal process dimension of the performance appraisal system (Luu, 2012a). In addition, the reliance on self-report data may produce common method bias (Podsakoff et al, 2012).…”
Section: Limitations and Future Research Pathsmentioning
confidence: 99%
“…The healthcare sector differs from other organisations since it requires a balance between cost-efficiency, quality, and customer service [9]. Implementing the BSC also demands a significant change in organisational culture, leadership style, and beliefs [10]. Rabbani et al (2011) asserted that the success of BSC implementation is determined by several factors, including participatory culture, leadership support, financial and non-financial incentives, and the integration of BSC policies into the organisations' resources and routine operational activities [11].…”
Section: Discussionmentioning
confidence: 99%